On the Importance of Family, Morality, Masculine, and Feminine Honor for Theory and Research. Issue 8 (August 2016) - Rodriguez Mosquera, Patricia M.
Abstract: This paper presents an approach to honor as multifaceted. In this approach, honor is defined as having four different facets, or honor codes: morality‐based honor, family honor, masculine honor, and feminine honor. The honor‐as‐multifaceted approach has generated much psychological research examining the importance of each honor code across different cultural and social groups. An overview of this research shows that that the different honor codes exert a powerful influence on a variety of group processes, including collective action, in‐group identification, the definition of gendered roles within the family, in‐group responses to threats to collective honor, intergroup attitudes, and value change within groups. The paper discusses how defining and measuring honor as multifaceted ‐rather than as an unitary construct‐ provides a fuller understanding of honor's role in group life.